Genetic evidence for an Azotobacter vinelandii nitrogenase lacking molybdenum and vanadium. - Pau, R N (1989)
We have constructed a strain of Azotobacter vinelandii which has deletions in the genes for both the molybdenum (Mo) and vanadium (V) nitrogenases. This strain fixed nitrogen in medium that did not contain Mo or V. Growth and nitrogenase activity were inhibited by Mo and V. In highly purified medium, growth was limited by iron. Addition of other metals (Co, Cr, Cu, Mn, Ni, Re, Ti, W, and Zn) did not stimulate growth. Like the V-nitrogenase, the nitrogenase synthesized by the double deletion strain reduced acetylene to both ethylene and ethane (C2H6/C2H4 ratio, 0.046). There was an approximately 10-fold increase in ethane production when Mo was added to the deletion strain grown in medium lacking Mo and V. This change in reactivity may be due to the incorporation of an Mo-containing cofactor into the nitrogenase synthesized by the double-deletion strain. A strain synthesizing the V-nitrogenase did not show a similar increase in ethane production. The growth characteristics of the double-deletion strain, together with the metal composition reported for a nitrogenase isolated from a tungstate-tolerant strain lacking genes for the molydenum enzyme grown in the absence of Mo and V (J. R. Chisnell, R. Premakumar, and P. E. Bishop, J. Bacteriol. 170:27-33, 1988) show that A. vinelandii can synthesize a nitrogenase which lacks both Mo and V. Reduction of dinitrogen by nitrogenase can therefore occur at a center lacking both these metals.